PROSPEK PERDAGANGAN INTERNASIONAL DAN PERTUMBUHAN EKONOMI DI INDONESIA - Doni, Amsah Hendri; Sentosa, Sri Ulfa; Aimon, Hasdi (Program Studi Magister Ilmu Ekonomi, 2012)
Abstract This article focused on analyse (1) influence of labor force, exchange rate, consumer price index, policy of tariff import and growth of economics to international trade in Indonesia (2) influence of kapital net, labor force, and international trade to growth of economics in Indonesia.Data used time series data of (I year kuartal 1990Â -Â IV year kuartal 2009). This article use analyzer model equation of simultaneous with method of Two Stages Least Squared (TSLS). The result of research conclude that (1) labor force, exchange rate, consumer price index, and policy of import tariff have an effect on by signifikan to international trade in Indonesia. The increase of to labor force, rate, consumer price index, and policy of import tariff will be the increase of international trade in Indonesia and conversely. While growth of economics do not have an effect on signifikan to international trade in Indonesia (2) kapital net, labor force, and international trade have an effect on signifikan to growth of economics in Indonesia. If kapital net, labor force, and international trade is increase of hence growth of economics in Indonesia will experience of improvement and conversely. Keyword: international trade, growth of economics, labor force, exchange rate, ihk, and capital net.